How to promote agricultural technologies that generate positive environmental effects? Evidence on tree planting in Indonesia - Karina Brenneis; Bambang Irawan; Meike Wollni (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2022)
Agricultural technologies frequently have been introduced via subsidies to accelerate diffusion and spur adoption in the presence of market inefficiencies or missing information. Yet, for agricultural technologies that mainly generate positive environmental effects, it is not clear how to encourage adoption, maintenance, and additional investments most effectively. This study addresses this gap by introducing two policy interventions to foster tree planting in an oil palm hotspot in Indonesia. In the first treatment, oil palm farmers receive information about native tree planting and three different native tree seedlings for free (subsidy treatment). In the second treatment, oil palm farmers receive the same information and the opportunity to buy three different native tree seedlings through an auction (price treatment). Results from negative binomial regressions reveal that a full subsidy leads to higher tree planting at first, but the results from a double hurdle model show that conditional on being planted there is no significant difference in survival rates between the two treatments. Our results further show that conditional on tree planting farmers in the price treatment apply a higher number of maintenance practices than farmers in the subsidy treatment. Finally, the subsidy treatment has a significantly negative effect on additional planting efforts.
Keywords: 330; technology adoption; policy analysis; auction; subsidies; negative binomial estimation